BASIS collaboration with ICT ministry to capture international market for building digital Bangladesh - Ahona, Sumaiya Akhter (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.